Morbidity pattern and health seeking behaviour of the geriatric population in a rural area of district Faridabad, Haryana: a cross-sectional study - Gupta, Ekta; Thakur, Archana; Dixit, Shivam (International Journal Of Community Medicine And Public Health, 2019)
Background: The increase in life expectancy has resulted in changes in age composition of India and tripling of geriatric population in last 50 years. To provide adequate and comprehensive care to elderly, understanding their health problems and health seeking behavior is imperative. Hence, this study aimed to assess the morbidity pattern and health-seeking behavior and factors affecting them among geriatric population of a rural area of district Faridabad. Methods: A cross-sectional study was carried out among 300 elderly above 60 years of age in village Pali of Faridabad district for a period of 3 months. The list of elderly was obtained from health workers’ records and they were interviewed regarding socio-demographic factors, morbidity status and health seeking behaviour using a predesigned and pretested structured questionnaire. Results: Out of 300 subjects, 56% were females and 63% were in age group of 60-69 years. Overall 93.3% subjects had one or more morbidities with musculoskeletal disorders being most common (57.3%) followed by visual impairment and cataract (54.0%) and hypertension (49.0%). Morbidities were significantly higher among females (p= 0.006), divorced/separated (p=0.014) and illiterate elderly (p=0.026). 77.7% elderly preferred allopathic system of medicine with private facilities preferred by 40%. Conclusions: Morbidity load among elderly was very high and health seeking behaviour was poor. So, strong efforts are needed to provide them with comprehensive and specialised care so that they contribute to their maximum potential to our society. Primary healthcare strategies targeting elderly needs to be strengthened and area specific strategies need to be formulated.